Prasugrel in Children With Sickle Cell Disease. Issue 1 (January 2015) - Styles, Lori; Heiselman, Darell; Heath, Lori E.; Moser, Brian A.; Small, David S.; Jakubowski, Joseph A.; Zhou, Chunmei; Redding-Lallinger, Rupa; Heeney, Matthew M.; Quinn, Charles T.; Rana, Sohail R.; Kanter, Julie; et al.
<x xml:space="preserve">Abstract</x> Introduction: This phase 2 study was designed to characterize the relationship among prasugrel dose, prasugrel's active metabolite (Pras-AM), and platelet inhibition while evaluating safety in children with sickle cell disease. It was open-label, multicenter, adaptive design, dose ranging, and conducted in 2 parts. Part A: Patients received escalating single doses leading to corresponding increases in Pras-AM exposure and VerifyNow®P2Y12 (VN) platelet inhibition and decreases in VNP2Y12 reaction units and vasodilator-stimulated phosphoprotein platelet reactivity index. Part B: Patients were assigned daily doses (0.06, 0.08, and 0.12 mg/kg) based on VN pharmacodynamic measurements at the start of 2 dosing periods, each 14±4 days. Platelet inhibition was significantly higher at 0.12 mg/kg (56.3%±7.4%; least squares mean±SE) compared with 0.06 mg/kg (33.8%±7.4%) or 0.08 mg/kg (37.9%±5.6%). Patients receiving 0.12 mg/kg achieved ≥30% platelet inhibition; only 1 patient receiving 0.06 mg/kg exceeded 60% platelet inhibition. High interpatient variability in response to prasugrel and the small range of exposures precluded rigorous characterization of the relationship among dose, Pras-AM, and platelet inhibition. Safety: No hemorrhagic events occurred in Part A; 3 occurred in Part B, all mild and self-limited. Conclusions: Most children with sickle cell disease may achieve clinically relevant platelet inhibition with titration of daily-dose prasugrel.